Remaking Higher Education : Essays in Dissent - Sinha, Sharad (INDIAN EDUCATIONAL REVIEW, 2011)
This is the latest in the series of books written by Amrik Singh which deals with a lot of issues in higher education. The book has a foreword by Kuldip Nayar and is divided in 10 chapters. The author goes down the memory lane, recalls his experiences and becomes analytical and suggestive in this polemical study of state of higher education in India. The author strongly feels that the two serious mistakes which India made were to continue with the legal and educational system more or less as they were before 1947. The major issues highlighted in the introductory part is negligence of teaching profession and its management. He comments that having neglected constructive role of teacher education has resulted in poor syllabus for teacher education and non-availability of the right kind of education.